PENGARUH UMUR PERUSAHAAN, UKURAN PERUSAHAAN, DEWAN KOMISARIS, LEVERAGE, DAN PROFITABILITAS TERHADAP PENGUNGGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2008-2010 - Linda Santioso; Natasha Caesar Devona (Jurnal Akuntansi, 2012)
The purpose of this research is to examine the effect of corporate characteristic, consist of company age, firm size, size of board commissioner, leverage, and profitability to corporate sosial responsibility disclosure in corporate annual report. This research can explain the decision making about the corporate sosial responsibility disclosure done by manufacturing companies listed in IDX for the year 2008 â€“ 2010. The data used are in form of annual reports from 30 companies used as sample for the year 2008-2010. The statistical methods use in this research is multiple regressions. The results of this research shows that company age and size of board commissioner have significant effect to corporate sosial responsibility disclosure, while firm size, leverage and profitability have insignificant effect to corporate sosial responsibility disclosure.Â Keywords : Corporate Social Responsibility Disclosure, Company age, Firm size, Size of board commissioner, leverage, and profitability.Â